2010
DOI: 10.1002/cjg2.1578
|View full text |Cite
|
Sign up to set email alerts
|

Reduction to the Pole at the Geomagnetic Equator

Abstract: Reduction to the pole (RTP) is a standard part of magnetic data processing method, especially for large‐scale mapping. RTP operation can transform a magnetic anomaly caused by an arbitrary source into the anomaly that the same source would produce if it is located at the pole and magnetized by induction only. Interpretation of magnetic data can further be helped by RTP in order to remove the influence of magnetic latitude on the anomalies, which is significant for anomalies caused by crust. The solution of RTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
0
17
0
2
Order By: Relevance
“…Reduction to equator (RTE) is a useful and effective operation designed to transform a total magnetic intensity (TMI) anomaly caused by an arbitrary source into the anomaly that this same source would produce if it were located at the pole and magnetised by induction only [21]. Reduction to pole (RTP) converts the mag-netic field from the magnetic latitude where the Earth's field is inclined to that field at a magnetic equator where the inducing field is vertical [22]. When the field of the Earth is inclined, magnetic anomalies caused by induction are related to their sources asymmetrically, but when the Earth`s inducing field is vertical, the associated anomalies would be directly over their sources [20].…”
Section: Reduction To Equatormentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction to equator (RTE) is a useful and effective operation designed to transform a total magnetic intensity (TMI) anomaly caused by an arbitrary source into the anomaly that this same source would produce if it were located at the pole and magnetised by induction only [21]. Reduction to pole (RTP) converts the mag-netic field from the magnetic latitude where the Earth's field is inclined to that field at a magnetic equator where the inducing field is vertical [22]. When the field of the Earth is inclined, magnetic anomalies caused by induction are related to their sources asymmetrically, but when the Earth`s inducing field is vertical, the associated anomalies would be directly over their sources [20].…”
Section: Reduction To Equatormentioning
confidence: 99%
“…where A p (u, v) is the Fourier transform of these observed magnetic data; A c (u, v) is the Fourier transform of the vertical magnetic field; I and D are the inclination and declination of core field, respectively; (u, v) is the wavenumber corresponding to the (x, y) directions, respectively; and Ω = arctan(u/v) [22]. The RTE for low geomagnetic latitudes was applied to the magnetic anomaly data.…”
Section: Reduction To Equatormentioning
confidence: 99%
“…This makes interpretation of magnetic anomalies complex. However, at low magnetic latitude, Luo et al [13] proposed special reduction to equator, which transforms the observed magnetic anomaly at the equator into an anomaly that would have been measured if the magne-tisation and ambient field were both vertical. This operation transforms theoretical magnetic anomalies located at the pole and magnetised by induction only into the observed magnetic anomalies.…”
Section: Reduced-to-equator (Rte) Mapmentioning
confidence: 99%
“…The desired improvements in the quality of the aeromagnetic data were achieved by the application of two-dimensional fast Fourier transform technique. In 2010, Luo et al [13] assumed the set of observed magnetic data acquired on planar observation surface. Earlier work done by Gun [14] was adopted, where reduction-to-pole operation in wave number domain was performed, given as Equation 1: D -Ɵ is close to ±90, which makes the imaginary part close to zero; thus, reduction-to-pole processing will be unstable at low latitudes and singular at the equator.…”
Section: Reduced-to-equator (Rte) Mapmentioning
confidence: 99%
See 1 more Smart Citation